Heart rate variability response to affective pictures processed in and outside of conscious awareness: Three consecutive studies on emotional regulation - YORGUNER, NEŞE (ELSEVIER, 2018)
Previous research has increased understanding of the neurobiological basis of emotional regulation. However, less is known concerning the unconscious processing of affective information. Three experiments were performed to investigate the extent to which complex affective stimuli can be processed outside of consciousness and demonstrate possible mechanisms for regulation of resulting emotional responses. In Experiment 1, participants were either instructed to passively observe blocked-picture cues (neutral and negative) or to down regulate their emotions by distancing. Resulting emotional regulation activity was assessed with 0.1-Hz heart rate variability (HRV) indices. In Experiment 2, participants were presented with affective pictures that were rendered consciously invisible by means of continuous flash suppression (CFS). In Experiment 3, two equivalent sets of negative affective pictures were covertly presented and the effect of a cognitive task on emotional regulation was evaluated. Our findings revealed that 0.1-Hz HRV indices exhibited greater change over baseline in response to negative compared to neutral stimuli for both presentation conditions (consciously perceived or not). The implementation of distancing and the cognitive task were both associated with higher 0.1-Hz HRV change scores. These results indicate that even complex affective stimuli can be processed without awareness, resulting in a congruent emotional response that is physiologically detectable. Cognitive strategies can help more effectively regulate this response, implying that conscious perception of a triggering stimulus may not be essential for cognitive regulation.
Keywords: AMYGDALA RESPONSE; STIMULI; FEAR; ANXIETY; FACES; EXPRESSIONS; MODULATION; DEPRESSION; STRESS; GENDER